2007
DOI: 10.1111/j.1524-4725.2007.33254.x
|View full text |Cite
|
Sign up to set email alerts
|

Digital Dermoscopic Monitoring of Atypical Nevi in Patients at Risk for Melanoma

Abstract: Background-Atypical nevi are a common risk factor for melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 22 publications
2
61
1
3
Order By: Relevance
“…On the other hand, in protocols of digital dermoscopy in which TBP are performed, body-maps are only registered in the first visits, and in subsequent controls body surface is simply compared with overview images. Already in 2007, Fuller et al 4 highlighted that it is unclear in most previous studies whether any MM was missed because they either presented as new lesions or arose from nevi that were not monitored by dermoscopy, since the total number of MM occurring in those patients was not reported. In the latter study, only one MM was detected by DFU out of 6 MMs detected during a median of 22 months; with a MM/benign lesion ratio of 1:94 and 1:34.4 among lesions with and without previous dermoscopy record respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in protocols of digital dermoscopy in which TBP are performed, body-maps are only registered in the first visits, and in subsequent controls body surface is simply compared with overview images. Already in 2007, Fuller et al 4 highlighted that it is unclear in most previous studies whether any MM was missed because they either presented as new lesions or arose from nevi that were not monitored by dermoscopy, since the total number of MM occurring in those patients was not reported. In the latter study, only one MM was detected by DFU out of 6 MMs detected during a median of 22 months; with a MM/benign lesion ratio of 1:94 and 1:34.4 among lesions with and without previous dermoscopy record respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been suggested that a screening strategy focused solely on atypical nevi will likely misdiagnose MM presenting as new lesions or corresponding to lesions not considered adequate for digital follow-up 4 .…”
Section: Introductionmentioning
confidence: 99%
“…A clinical study by an Australian group found that the biopsy ratios for general practitioners ranged from 82:1 for young patients to 10:1 for older patients. The biopsy ratio appears to be substantially reduced with the use of newer technologies such as dermoscopy, surface microscopy, and multispectral imaging (28,(30)(31)(32)(33)(34)(35)(36)(37)(38). Westerhoff and colleagues found that the accuracy of melanoma diagnosis could be improved from 63% to 76% with the aid of surface microscopy (30).…”
Section: Discussionmentioning
confidence: 99%
“…65,66 Whereas this approach appears sensitive for early melanoma detection in that a relatively higher percentage of melanomas were diagnosed as in situ, some melanomas might have been missed because they either presented as new lesions or arose from nevi that were not serially monitored. 67 Dermoscopy can increase or decrease confidence that a melanocytic lesion is benign or malignant, 68,69 thereby improving the early detection of melanoma, while reducing the need for unnecessary biopsies. 70,71 Regular annual follow up monitoring is also needed to detect slow-growing melanomas in which subtle changes may become apparent only over time.…”
Section: Using Technology To Augment Early Melanoma Diagnosis Dermoscopymentioning
confidence: 99%